PENGARUH PERCEIVED USEFULNESS, CONFIRMATION, DAN SATISFACTION TERHADAP CONTINUANCE INTENTION PENGGUNAAN FITUR LIVE STREAMING SHOPEE EIGER - Abdillah, Ibnu Zaki; Fadhilla, Hanifa Nur (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study aimed to analyze the effects of perceived usefulness, confirmation, and satisfaction on continuance intention in the use of Shopee live streaming features among Eiger product consumers. The rapid growth of e-commerce has driven changes in consumer behavior, where direct interaction through live streaming has become an important medium for building trust and user engagement. This study was grounded in the Expectation Confirmation Theory and the Technology Acceptance Model. A quantitative approach was employed using a survey of 150 respondents in Indonesia who had watched and purchased Eiger products through Shopee Live. Data were collected using a Likert-scale questionnaire and analyzed using variance-based structural equation modeling. The results show that perceived usefulness and confirmation positively influence satisfaction, and satisfaction significantly influences continuance intention. The findings confirm that perceived benefits and the alignment between actual experiences and initial expectations are key determinants in encouraging sustained use of live streaming features in e-commerce platforms. Future research is recommended to adopt a longitudinal design to capture changes in consumer perceptions and satisfaction over time. Keywords: Perceived Usefulness, Confirmation, Satisfaction, Continuance Intention, Eiger